Wisława Knapowska - Pioneer of Poznań’s History Didactics - Nowocin, Jakub (Sensus Historiae, 2025)
The article presents the achievements of Wisława Knapowska in history didactics. A biographical outline precedes the presentation of her pioneering activities in this subdiscipline of history, associated with the development of history didactics in Poznań. An analysis of two key texts by Knapowska, concerning the shaping of historical memory in school education and the training of future teachers, reveals that her ideas were ahead of her time and that their certain elements remain relevant in contemporary history didactics.